2017
DOI: 10.1111/epi.13812
|View full text |Cite
|
Sign up to set email alerts
|

Nonintravenous rescue medications for pediatric status epilepticus: A cost‐effectiveness analysis

Abstract: For pediatric status epilepticus, buccal midazolam and nasal midazolam are the most cost-effective nonintravenous rescue medications in the United States. Rectal diazepam is not a cost-effective alternative, and this conclusion remains extremely robust to wide variations of the input parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 34 publications
0
27
0
Order By: Relevance
“…13,14 Furthermore, surveys of clinical practice suggest that the most commonly used first-line treatment non-intravenous benzodiazepine (non-IV BZD)-rectal diazepam 14 -and the most commonly used second-line treatment non-benzodiazepine antiseizure medication (non-BZD ASM)-intravenous phenytoin/fosphenytoin 13 -are among the least-effective choices within their respective category. [7][8][9][10] Two recent randomized clinical trials (ConSEPT and EcLiPSE) showed that, consistent with the observational evidence, intravenous levetiracetam has a similar efficacy to that of intravenous phenytoin/fosphenytoin, but both with the lowest effectiveness among non-BZD ASMs. 15,16 The Established Status Epilepticus Treatment Trial (ESETT) found that intravenous levetiracetam, intravenous fosphenytoin, and intravenous valproate had a similarly low rate of success in the treatment of BZD-resistant SE, although their definition of success was a composite outcome of absence of seizures, improved responsiveness at 60 minutes, no need for additional ASMs, and no endotracheal intubation.…”
Section: Milton C Weinsteinmentioning
confidence: 66%
See 1 more Smart Citation
“…13,14 Furthermore, surveys of clinical practice suggest that the most commonly used first-line treatment non-intravenous benzodiazepine (non-IV BZD)-rectal diazepam 14 -and the most commonly used second-line treatment non-benzodiazepine antiseizure medication (non-BZD ASM)-intravenous phenytoin/fosphenytoin 13 -are among the least-effective choices within their respective category. [7][8][9][10] Two recent randomized clinical trials (ConSEPT and EcLiPSE) showed that, consistent with the observational evidence, intravenous levetiracetam has a similar efficacy to that of intravenous phenytoin/fosphenytoin, but both with the lowest effectiveness among non-BZD ASMs. 15,16 The Established Status Epilepticus Treatment Trial (ESETT) found that intravenous levetiracetam, intravenous fosphenytoin, and intravenous valproate had a similarly low rate of success in the treatment of BZD-resistant SE, although their definition of success was a composite outcome of absence of seizures, improved responsiveness at 60 minutes, no need for additional ASMs, and no endotracheal intubation.…”
Section: Milton C Weinsteinmentioning
confidence: 66%
“…[4][5][6] Choosing the treatment with the highest effectiveness, that is, the highest probability of stopping seizures early, may reduce the downstream clinical and economic burden of SE. However, limited evidence and substantial uncertainty on the effectiveness of different treatment options [7][8][9][10] translates into treatment guidelines that do not recommend any particular treatment as the best option. 11,12 Therefore, many treatment choices for SE are based on tradition and expert opinion.…”
Section: Milton C Weinsteinmentioning
confidence: 99%
“…58 A cost-effectiveness analysis in the United States suggested that buccal midazolam and intranasal midazolam were the most cost-effective non-IV alternatives, and rectal diazepam was not a cost-effective choice by a large margin. 59 Another study compared intranasal midazolam and rectal diazepam and found a better cost-effectiveness profile in the intranasal midazolam group. 60 Regarding preferences of caregivers about the use of one drug or another, one study revealed an overall better acceptance of intranasal midazolam over rectal diazepam due to the ease of use, efficacy, and comfort of the intranasal formulation.…”
Section: Time To Treatmentmentioning
confidence: 99%
“…61 Remarkably, the Food and Drug Administration (FDA) approved rectal diazepam only for the treatment of acute repetitive seizures. 59,[61][62][63][64] Therefore, its use for prolonged seizures and SE remains off-label. 59,61 Its FDA approval was based on clinical trials that looked at the response of rectal diazepam reducing the frequency of acute repetitive seizures over many hours.…”
Section: Time To Treatmentmentioning
confidence: 99%
See 1 more Smart Citation